Evaluation of Salicylic acid Pre-Hardening Treatments of Cowpea for Resistance against the Flea Beetle, Podagricafuscicornis Linn. (Coleoptera: Chrysomelidae) - A. H., Audi; F. B., Mukhtar (International Journal of Environment, Agriculture and Biotechnology, 2019)
The experiment was conducted to evaluate the potential of SA-treatment in the control of Pod sucking bug of cowpea. The mean annual rainfall was within the range of 865-1250mm with mean annual temperature of about 22-38°C and relative humidity of 65-90mmHg. Four different cowpea varieties (IT97K-1069-6, IT98K-205-8, IT89KD-288 and Dan’ila) pre-hardened with Salicylic acid were established in various replicated field cages in completely randomized design. Five-pairs each of fresh pre-mated bugs were introduced into the various cages, allowed for 2-weeks to mate and oviposit after which all adult insects are removed. The different cowpea varieties screened showed variable response to the bug attack. IT97K-1069-6 and IT89KD-288 recorded lower indices of susceptibility and leaf damage to flea beetle attack, delayed development time of larvae with few progeny emergence. Pre-treatment effects also varied significantly (P<0.001) with higher concentrations (10ppm) of Salicylic acid (SA) being more effective in reducing leaf damage than the lower (5ppm) concentrations and the controls. The interaction of treatments and varieties was also found significant (P<0.002). Of the four Cowpea varieties screened, IT97K-1069-6 and IT89KD-288 pre-hardened with 10ppm of SA were found tolerant owing to their low susceptibility indices (7.09 and 9.09) and percentage leaf damages (18.58% and 25.93% respectively while Dan’ila and IT98K-205-8 treated from the same concentrations were however susceptible. Phytochemical analysis of treatments showed high concentrations of eugenol and sesquiterpenes in the tolerant varieties. These relations should be explored extensively toward sustainable plant protection.